The Russian Oil and Gas Sector in the Projection of Modern Transformational Trends - E. A. Kuklina; A. D. Palchik (Управленческое консультирование)
The relevance of the research topic is due to the role and importance of the results of the activities of enterprises in the oil and gas sector, which is currently strongly influenced by modern transformational trends, for the development of the national economy. The article analyzes the results of the impact of the green trend, due to the objective need to follow the principles of ESG and respond to the challenges of decarbonization.The purpose of the study is to study the impact of the green agenda and evaluate the effectiveness of ESG investments, as well as substantiate proposals for the implementation of ESG principles in corporate strategies of oil and gas companies.Research objectives: to study the green cases of key Russian oil and gas companies; to evaluate the effectiveness of ESG investments; to formulate proposals that allow companies in the oil and gas sector to integrate more effectively into the ESG agenda.Research methods: systematic approach, logical analysis, synthesis; The empirical method of rating assessment, content analysis of open sources, correlation and regression analysis were used.Results. Despite the improvement of positions in profile ratings, the profitability of ESG investments is unstable, therefore, it is necessary to strengthen work to increase the level of environmental and social responsibility, and the effectiveness of risk management. It is necessary to consolidate at the legislative level the requirements for reporting on sustainable development, which still do not fully comply with international standards in the criteria part. Evaluating the effectiveness of ESG investments is complicated by several problems caused by the use of various approaches to integrating ESG principles and monitoring this process using KPIs, insufficient activity in tracking and disclosing information about the effectiveness of ESG strategies, etc.The main conclusions. The successful and consistent solution of the tasks of green energy transfer allows us to achieve the application of corporate strategy methods and operational efficiency methods for key vectors. There is a high correlation between the indicators of ESG investments and the net profit of oil and gas companies; PJSC Tatneft and PJSC NK Rosneft have the most significant correlation coefficient. It is advisable to develop a document at the level of industry regulators that includes a package of preferences for oil and gas companies implementing the ESG agenda (tax incentives, provision of long-term and cheap financing by infrastructure state banks, accelerated depreciation of capital investments in ESG projects, ensuring stable financing of joint projects in the field of sustainable development of the regions where oil and gas companies are based).